If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5 = 5 + 4 Reorder the terms: -5 + 4x = 5 + 4 Combine like terms: 5 + 4 = 9 -5 + 4x = 9 Solving -5 + 4x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 4x = 9 + 5 Combine like terms: -5 + 5 = 0 0 + 4x = 9 + 5 4x = 9 + 5 Combine like terms: 9 + 5 = 14 4x = 14 Divide each side by '4'. x = 3.5 Simplifying x = 3.5
| (x)(-x+32)=48 | | 10x+2=-14 | | -15+(-6)-19= | | 36x^2+y^2+36z^2=36 | | 0=-4t^2+6t-1 | | 2k^3-8k=0 | | -6x+0=24 | | 4x-4y=-72 | | 3q^2+a-14=0 | | -6(-4+y)+y=24 | | ln(5x-10)=ln(19) | | ln(5x+10)=ln(19) | | 0.7x-0.3=0.6x+5 | | -40+9x=-11x+4(5x+12) | | 9=1a/7a | | -4x+4y=16 | | 232+6(log)x=190 | | x+y+2y=45 | | -27.0=-4.5c | | -6x+y=24 | | -2x^2+5=3x-3 | | 51=x+4x+(x+3) | | -4(4)+4y=16 | | 6+z*10=-2 | | 2x/7x=3 | | x(15x+4)=32 | | 6x-6=4x+10 | | 2x/8x=3 | | f(x)=x^3+6x^2+3x-10 | | -6(4)+y=24 | | -12(2n+11)=3(5n-5) | | 6x-1=27-x |